South African midwives caring for immigrant and refugee women - Koneshe, M (Refugee Studies Centre, University of Oxford, 2016)
Over recent years South Africa has accepted many refugees and asylum seekers, among whom are women requiring maternity services. Because the values and cultural practices of immigrant pregnant women sometimes differ from those of the midwife, their rights to good treatment may be violated.